A Case Report on Alcohol Withdrawal Syndrome (International Journal of Ayurveda and Pharma Research, 2024)
Heavy drinkers who abruptly cut back on their alcohol intake or give it up entirely risk experiencing alcohol withdrawal. The warning signs and symptoms include agitation, anxiety, irritability, and mild to moderate tremors. Seizure, hallucinations, delirium tremens are the most severe withdrawal symptoms. These symptoms arise from abnormalities in brain chemistry brought on by alcohol, which leads to an excess of neuronal activity when the alcohol is stopped. Ayurveda is a holistic approach which not only takes body into consideration but also mental status. Madatyaya is a wide term explained in our classics, while explaining Madya, Acharaya told that it has properties opposite to that of Ojus, so these substances causing depletion to our body resources can be correlated to Madatyaya. So it’s a case report on alcohol withdrawal symptoms and its effective management using Ayurvedic treatment modalities.